Knowledge and readiness of teachers in implementing augmentative and alternative communication - Sipho Sibanda; Brilliant Mhlanga (Springer, 2024)
Abstract This qualitative study critically examines the knowledge and readiness of teachers in South African classrooms in utilising Augmentative and Alternative Communication (AAC) for learners facing communication challenges. The study addresses the concerns expressed by teachers regarding their lack of knowledge and skills in utilizing AAC, highlighting the crucial role of teacher readiness in successfully implementing this approach. The findings demonstrate that many teachers in South Africa feel ill-equipped to work with learners who rely on AAC due to limited resources and inadequate training. To ensure the effective use of AAC in classrooms and extend access to communication aids for all students, efforts are needed to enhance teacher training and support.This study also explores the challenges involved in implementing AAC exclusively within the school environment, emphasizing the importance of extending AAC usage to learners' homes for skill sharing and relevance in daily life. Additionally, the impact of staff turnover on AAC implementation in schools is examined, underscoring the necessity of addressing turnover rates and providing sufficient training to ensure successful integration of AAC. Overall, this study emphasizes the significance of incorporating AAC in the classroom and the need to equip teachers with the necessary resources and training to effectively support AAC learners both in the classroom and beyond. The research adopts a single-case study design, focusing on a Primary School in Johannesburg East, South Africa.